ANALISIS KEJAHATAN BEGAL DENGAN MOTIVASI PERAMPOKAN DI KOTA PALU - Dirgantara, Ryan (Universitas Tadulako, 2020)
The research problem is the cause of robbery criminal act in Palu and the obstacles faced by law enforcement officials in eradicating the criminal act of robbery in Palu City. The analytical method used in this research was data analysis in which the results of the research are the factors causing the robbery criminal act in Palu, namely the influence of inadequate economic needs the rise of consumerism and materialism, media, weak social supervision, Bullying, hoodlum, education,unfavorable environment, cultural differences, religious factors, and waves of urbanization. The constraints faced by law enforcement officials in eradicating robbery criminal act in Palu are lack of information, psychological conditions of victims,time and location, absence of perpetrators (still in the investigation), lack of community participation, and lack of witnesses and goods evidence.